Changes in visual cortical processing attenuate singleton distraction during visual search. (November 2020) - Won, Bo-Yeong; Forloines, Martha; Zhou, Zhiheng; Geng, Joy J.
Abstract: The ability to suppress distractions is essential to successful completion of goal-directed behaviors. Several behavioral studies have recently provided strong evidence that learned suppression may be particularly efficient in reducing distractor interference. Expectations about a distractor's repeated location, color, or even presence are rapidly learned and used to attenuate interference. In this study, we use a visual search paradigm in which a color singleton, which is known to capture attention, occurs within blocks with high or low frequency. The behavioral results show reduced singleton interference during the high compared to the low frequency block (Won et al., 2019). The fMRI results provide evidence that the attenuation of distractor interference is supported by changes in singleton, target, and non-salient distractor representations within retinotopic visual cortex. These changes in visual cortex are accompanied by findings that singleton-present trials compared to non-singleton trials produce greater activation in bilateral parietal cortex, indicative of attentional capture, in low frequency, but not high frequency blocks. Together, these results suggest that the readout of saliency signals associated with an expected color singleton from visual cortex is suppressed, resulting in less competition for attentional priority in frontoparietal attentional control regions.